The Clinical Value of Salivary Aldosterone in Diagnosis and Follow-Up of Primary Aldosteronism - Lichtenauer, U. D.; Gerum, S.; Asbach, E.; Manolopoulou, J.; Fourkiotis, V.; Quinkler, M.; Bidlingmaier, M.; Reincke, M. (Hormone and Metabolic Research, 2016)
Primary aldosteronism (PA), the most common form of secondary hypertension, causes relevant morbidity. The value of salivary measurements of aldosterone in clinical routine in PA so far has not been assessed. First, we analyzed salivary and plasma aldosterone concentrations of 42 patients with PA and 37 hypertensive controls (HC) during a sodium infusion test prospectively. Second, morning salivary and plasma aldosterone concentrations as well as diurnal saliva aldosterone profiles were analyzed in 115 patients treated for PA (46 adrenalectomy, 56 spironolactone, 13 eplerenone). Salivary aldosterone was substantially elevated in PA patients compared to HC at baseline (106±119 vs. 40±21 ng/l, p=0.01), and after 4-h sodium infusion test (60±36 vs. 23±14, p=0.01). Positive correlation between salivary and plasma aldosterone levels was evident, with exception of concentrations in or below the lower normal range. Applying a salivary aldosterone cutoff of 51.2 ng/l, found by ROC curve analysis, rendered a sensitivity of 81% and a specificity of 73% for PA. The diurnal rhythm of aldosterone was preserved in untreated PA patients, but concentrations were higher in the context of PA, and normalized after surgery (118±57 vs. 31±18 ng/l, p<0.01). Taken together, salivary aldosterone measurements correlate with plasma levels, allowing simple and cost effective assessments of aldosterone secretion in an outpatient setting. Nevertheless, as this method alone cannot replace other plasma parameters, and as aldosterone profiling would not alter diagnostic or treatment strategies, salivary aldosterone measurements in routine practice are of limited clinical value.
Keywords: aldosterone; rennin; Conn’s syndrome; hypertension; saliva; aldosterone producing adenoma